The Effectiveness of Reality Therapy to Increase Self-Esteem in Former Female Migrant Workers Beneficiaries at the Margo Widodo Social Service Center in Semarang - Runaweri, Heni Silva; Wibhowo, Christin (Journal of Law, Politic and Humanities, 2025)
The Female Migrant Workers (TKW) Group is a group that works to meet economic needs, as well as the influence of the surrounding environment. After quitting and not having a job, some of this group continue to live as PM in Social Institutions. Former TKW tend to look down on themselves, have a pessimistic outlook on life, are not enthusiastic, have difficulty socializing because they feel useless, feel guilty about themselves, and regret their current life so that this group experiences low self-esteem. One way that can help improve the self-esteem of the PM group is Reality Therapy. The purpose of this study was to determine the effectiveness of reality therapy using the WDEP (What, Doing, Evaluating, Planning) technique to increase self-esteem in PM Mantan TKW at the Margo Widodo Social Service Center in Semarang. This research method is a quasi-experiment, with a pattern matching data analysis technique. Participants in this study were 5 PM Mantan TKW. The self-esteem instrument used was Rosenberg Self Esteem in the form of a pre-test and post-test. Based on the results of the pre-test, 5 participants showed low self-esteem. After the application of Reality Therapy to the PM Mantan TKW group, there was an increase in self-esteem, this was supported by the results of the post-test which showed that 5 participants had normal category self-esteem. The following are the results of the pre-test and post-test for each participant, with a score classification from RSES 0-14 low, 15-25 normal, 26-30 high. Participant MH had an RSES score of 14 to 19, participant DA 12 to 16, KI score 11 to 16, BI score 11 to 15, and SN score 12 to 17. Based on the results found before and after the intervention, it can be concluded that WDEP technique reality therapy is effective in helping to improve self-esteem in PM Former Female Migrant Workers at the Margo Widodo Social Service Center in Semarang.